A general expression of the price of an American options using the Malliavin derivative. Issue 5 (2nd September 2016) - Kharrat, Mohamed
Abstract: The aim of this paper is to elaborate a general expression of the conditional expectation related to pricing problem of the American options using the stochastic integration by parts ( Malliavin derivative). This work is a generalization of the Jerbi and Kharrat's work (2013). Basing on the density function of the asset price, Jerbi and Kharrat used the Malliavin calculus to give the expression of the conditional expectation related to pricing American option problem, but in this work we use the stochastic integration by parts in order to resolve the previous problem.